6(x-4)+3=-3x-3

Simple and best practice solution for 6(x-4)+3=-3x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-4)+3=-3x-3 equation:


Simplifying
6(x + -4) + 3 = -3x + -3

Reorder the terms:
6(-4 + x) + 3 = -3x + -3
(-4 * 6 + x * 6) + 3 = -3x + -3
(-24 + 6x) + 3 = -3x + -3

Reorder the terms:
-24 + 3 + 6x = -3x + -3

Combine like terms: -24 + 3 = -21
-21 + 6x = -3x + -3

Reorder the terms:
-21 + 6x = -3 + -3x

Solving
-21 + 6x = -3 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-21 + 6x + 3x = -3 + -3x + 3x

Combine like terms: 6x + 3x = 9x
-21 + 9x = -3 + -3x + 3x

Combine like terms: -3x + 3x = 0
-21 + 9x = -3 + 0
-21 + 9x = -3

Add '21' to each side of the equation.
-21 + 21 + 9x = -3 + 21

Combine like terms: -21 + 21 = 0
0 + 9x = -3 + 21
9x = -3 + 21

Combine like terms: -3 + 21 = 18
9x = 18

Divide each side by '9'.
x = 2

Simplifying
x = 2

See similar equations:

| 8xz=50.00 | | 15(5+5y)=415+y | | 3z+4=7z+2 | | X^2-2x+10=9 | | y=x^5-x^3-12x | | -6(f-89)=-30 | | (x-1)(-3-2i)(-3+2i)=0 | | -6x+11x-59=41 | | b-5=14 | | (8x-7)(3t+9)=0 | | 2(s+3)+4s-5=148+s | | 7h+9j-3h-j= | | 5x-4y=39 | | 4x+6-11x=8 | | 144x-54=18(8x-3) | | 4x-6x+21=5x+35 | | 4x-10+9+6x=34 | | x+1=3+x | | -8d+1=-3 | | 4(x-6)=-3x-17 | | 4x+8-7x+2=5x-8x+7 | | 24x-4+3=24x+12-10 | | 5-3n=10 | | 3x=12x^2 | | 80-k=41 | | 3x-4y=16*x | | 2x^2+4x-4=-6 | | 6(4b-2c)+9f= | | 5y^2-40y^2=0 | | 10(t-4)+4t=7(2t-5)-9 | | 6x+4=6x-9 | | 3x-6+4x-3=180 |

Equations solver categories